Comparison on In Vitro Characterization of Fucospheres and Chitosan Microspheres Encapsulated Plasmid DNA (pGM-CSF): Formulation Design and Release Characteristics - SEZER, ALİ DEMİR (SPRINGER, 2009)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a cytokine used in the treatment of serious conditions resulting from chemotherapy and bone marrow transplantation such as neutropenia and aplastic anemia. Despite these effects, GM-CSF has a very short biological half-life, and it requires frequent injection during the treatment. Therefore, the cytokine production is possible in the body with plasmid-encoded GM-CSF (pGM-CSF) coding for cytokine administered to the body. However, the selection of the proper delivery system for the plasmid is important. In this study, two different delivery systems, encapsulated plasmid such as fucoidan-chitosan (fucosphere) and chitosan microspheres, were prepared and the particle physicochemical properties evaluated. Fucospheres and chitosan microspheres size ranges are 151-401 and 376-681 nm. The zeta potential values of the microspheres were changed between 8.3-17.1 mV (fucosphere) and +21.9-28.9 mV (chitosan microspheres). The encapsulation capacity of fucospheres changed between 84.2% and 94.7% depending on the chitosan molecular weight used in the formulation. In vitro plasmid DNA release from both delivery systems exhibited slower profiles of approximately 90-140 days. Integrity of released samples was checked by agarose gel electrophoresis, and any additional band was not seen. All formulations were analyzed kinetically. The calculated regression coefficients showed a higher r (2) value with zero-order kinetics. In conclusion, the characterizations of the microspheres can be modulated by changing the formulation variables, and it can be concluded that fucospheres might be a potential carrier system for the controlled delivery of GM-CSF encoding plasmid DNA.
Keywords: chitosan; fucoidan; GM-CSF; microsphere; plasmid; COMPLEX-FORMATION; GM-CSF; DELIVERY; NANOPARTICLES; CARRIERS; VACCINE; ACID)